Mood Disorders - Kocabasoglu, Nese (IntechOpen, 2013)
Mood disorders are a crucial group of mental disorders that last for a life time, cause psychosocial dysfunction, disrupts interpersonal relationships and are overall highly restrictive. The facts that mood disorders are seen as high as 3-5% of the society and 70% of the patients' first psychiatric application puts forward that they are not well known show that these are a serious type of mental illness. The average time to make the right diagnose is reported as 10 years. The delays in diagnose and beginning of treatment lays a heavy burden on the patient, their relatives and society in general. After the diagnose begins the process of selecting the right treatment method of each individual which is of high importance as to enable the patient go through their treatment period without mental exhaustion. Protecting treatment planning and management in long term treatments are significant for the control of the disorder. Difficulties are frequently experience during diagnose, treatment and follow up for mood disorders. Professional constantly seek for innovations to resolve these issues in treating mood disorders. In this context, we hope that this book will become an important resource of some new researches for clinicians.